PENGARUH MODEL PERILAKU KONSUMEN TERHADAP NIAT BELI PADA PRODUK BERLABEL HALAL - Fadhil Kamal; Sri Padmantyo (POLITEKNIK LP3I JAKARTA, 2025)
Increasing consumer awareness of halal products makes it important to study the factors that influence purchase intention of halal-labeled products. This study assesses the influence of attitude, knowledge, religiosity, subjective norms, halal labels, and behavioral control on purchase intention. This study uses a quantitative approach with a purposive sampling method, targeting respondents aged over 18 years and Muslim. The questionnaire was distributed via Google Form using a Likert scale. Referring to Hair et al. (2019), the minimum sample size is determined five times the number of indicators, namely 155 respondents from 31 indicators. In its implementation, 252 respondents were obtained. The data were analyzed using the SEM-PLS method which then resulted in the finding that Knowledge and religiosity have a significant effect on attitudes, with religiosity as the dominant factor. Attitudes, subjective norms, and perceived behavioral control have a significant effect on the perception of the importance of halal labels and purchase intention. The halal label has a direct effect on purchase intention and partially mediates the relationship between attitudes, subjective norms, and behavioral control with purchase intention, with the strongest mediation through subjective norms